A Study on Magneto-thermodiffusive Wave Propagation in Dual-phase-lag Thermoelasticity with Temperature-dependent Properties - Rajesh Kumar; Gaurav Gupta; Amita Bhagat; Kapil Kumar Kalkal (International Journal of Mathematics And its Applications, 2018)
The present paper is concerned with the analysis of magneto-thermodiffusive wave propagation in a homogeneous, isotropic, thermally and perfectly conducting elastic medium with temperature dependent mechanical properties. The formulation is established under the purview of dual-phase-lag thermoelasticity theory with diffusion. The modulus of elasticity is taken as a linear function of reference temperature. The resulting non-dimensional coupled equations are applied to a specific problem of a half-space whose surface is subjected to a time dependent mechanical shock. The analytical expressions for the displacement components, stresses, concentration and temperature field in the physical domain are obtained by employing normal mode analysis. Finally, numerical solution is carried out for copper material and corresponding graphs are plotted to illustrate and compare theoretical results. Discussions have been made to highlight the effects of phase lag parameters, temperature dependent modulus of elasticity, frequency and time on the physical fields. Some particular cases of interest have been deduced from the present investigation. The phenomenon of a finite speed of propagation is observed graphically for each field.